SCHWARZ BIN ICH UND SCHÖN – RHETORISCHE IRONIE IM HOHELIED1 - S Fischer (Acta Theologica)
BLACK AM I AND BEAUTIFUL – RHETORICAL IRONY IN SONG OF SONGS This article argues for an ironic understanding of Song of Songs 1:5-6. The linguistic irony carries a second meaning contrary to the first more obvious one, being expressed as verbal and situational irony. The rhetorical structure and the figures of speech are analyzed. The stereotype conceptualizations of “blackness” and “beauty” in the Old Testament are evaluated. It is demonstrated that she boasts of being black and beautiful. The text is explained by the stylistic device of rhetorical irony. This leads to the result that she is also a city woman and that the vineyard-episode with her brothers (1:5-6) cannot be understood as a serious explanation for her skin colour, as it commonly happens. Perhaps she is associated with Pharaoh’s daughter. Finally, the second conflict with her brothers (8:8-12) is taken into account and it is shown how the “Kipp-Phänomen” is used to turn around the expectations of those involved in comic and irony.